2015
DOI: 10.17507/tpls.0510.10
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Written Corrective Feedback on Writing Accuracy of Intermediate Learners

Abstract: Abstract-The present research examined the role of written corrective feedback (WCF) in enhancing writing accuracy of Iranian Intermediate learners. The present study is quantitative and experimental survey that measured the accuracy of using two functions of English article system, namely definite article "the" and indefinite article "a" and "an" during eight weeks using pre-test and post-test. Sixty students including (20 control group, 20 experimental group,20 experimental group) participated in the study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 11 publications
7
17
0
Order By: Relevance
“…Bitchener (2008) also states that written corrective feedback benefits EFL writers' writing performance in both short and long term. Later, Sarvestani and Pishkar (2015) point out that written feedback type assists students to accurately use English articles.…”
Section: Teacher Corrective Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…Bitchener (2008) also states that written corrective feedback benefits EFL writers' writing performance in both short and long term. Later, Sarvestani and Pishkar (2015) point out that written feedback type assists students to accurately use English articles.…”
Section: Teacher Corrective Feedbackmentioning
confidence: 99%
“…Both feedback types can be in the written and verbal forms. Previous studies (Ferris & Robert, 2001;Hosseiny, 2014;Sarvestani & Pishkar, 2015;Tootkaboni & Khatib, 2014) have indicated that both types of teacher feedback benefit student writers' writing development.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In general, the most common corrective feedback (CF, henceforth) can be categorized into two: direct feedback and indirect feedback (Walz, 1982;Bates, Lane & Lange, 1993;Ferris & Hedgcock, 1998;Eslami, 2014). Both types of corrective feedback in written and oral forms have been proven to be beneficial in students' writing process (Tootkaboni & Khatib, 2014;Sarvestani & Pishkar, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Another possible interpretation of the result is that direct corrective feedback was very time-saving as it provided the learner with the correct linguistic structure above or beside the linguistic error. As a consequence, the students were able to figure out the differences between the two forms, the erroneous and the correct one, which might polish the blur image in the mind of the learner in relation to the usage of the target grammatical aspect (Sarvestani, & Pishkar, 2015;Sun, 2013). Furthermore, as the learners' time was saved, they did not copy and paste the right form instead of the erroneous one, but they might revisit the rule governing the errors made which, in turn, enabled them to apply thoroughly the same rules in the encountered similar situations.…”
Section: Discussionmentioning
confidence: 99%